Parents' Understanding of Additive Synthetic Through Healthy Lunch-Box Parenting Practice - Innayah, Devi Sholihatun; Mukminin, Amirul (Indonesian Journal of Early Childhood Education Studies, 2018)
Food plays an important role in providing energy and nutrient supplies for children. The consumption of school's snacks is important due to children's high activities. The problem in this study is whether there is a difference in parental understanding of synthetic additives through parenting of healthy lunch-box and whether there is an increase in parents' understanding of synthetic additives through healthy lunch-box parenting. This study aims to determine differences in parental understanding of synthetic additives through healthy lunch-box parenting. This study also purposes to find out the improvement of parents' understanding of synthetic additives through healthy parenting supplies. The research is quantitative with the experimental method with one group pretest-posttest design. The method of data collection is questionnaires and observations. The type of the data is ordinal. The sampling technique is a simple random sampling. This research is conducted at PGRI 42 Jomblang Kindergarten with 30 research subjects who are parents or students' guardians. The results in this study show the hypothesis test using SPSS statistics 23 calculation. Then the t-test test data is obtained through a different paired sample t-test on the program with a value of t -1.356 with a 2-tailed significance value of 0.000. It can be assumed that H(a) is accepted because of the significance value <0.05. This means that there is a difference in parents' understanding in the PGRI 42 Jomblang Kindergarten in Semarang City regarding synthetic additives through lunch-box parenting. From the results of the improvement test, H(b) is accepted, the level of understanding of parents has increased by 5.11%, this can be seen from the results of calculations with percentage techniques.